The Lymphomas - Canellos, George P; Lister, T. Andrew; Sklar, Jeffrey L (Saunders, 1998)
B. Saunders. Harvard Univ., Boston, MA. Extensive text on the basic science and clinical aspects of lymphomas. For practitioners and researchers. 46 contributors, 35 U.S. Halftone illustrations, color plates. DNLM: Lymphoma.
Keywords: Neoplasms; Lymfomy; nádory; lymfom; Lymphoma; hematologie; Hematologie onkologická; Hematology; onkologie